Pengaruh Tren Globalisasi di Indonesia Pada CV. Alumunium Mufido Jaya : Tantangan dan Dampak nya Terhadap Keputusan Pembelian - Afifah Faiza Kamilah Muis; Hadita Hadita (Global Leadership Organizational Research in Management, 2024)
The purpose of this research is to find out the influence of Globalization, Challenges, Impact on CV Purchasing Decisions. Mufido Jaya Aluminum in Bekasi. The study method uses qualitative analysis, namely through primary data produced from observation, a data collection method that involves direct observation of certain actions, events or objects. In this era of globalization, business actors are required to be able to compete to maintain the continuity of superior institutions on an ongoing basis, both in the short term and in the long term, which can influence the challenges and impacts of this performance. Therefore, the problems faced in this research are (1) Identifying globalization trends, (2) Identifying challenges to CV. Mufido Jaya, (3) Analyzing the impact of globalization trends on CV business. Mufido Jaya. The results of this research can be concluded that the influence of purchasing decisions is (1) due to meeting consumer needs and tastes, (2) competition from competitors from the same business, (3) due to fluctuating economic conditions in Indonesia.(4) The impact of globalization trends on CV. Mufido Jaya, (5) Challenges from the surrounding environment.